Assessment of sideband energy ratio technique in detection of wind turbine gear defects. (December 2015) - T.R., Pattabiraman; K., Srinivasan; K., Malarmohan
Abstract: Gearbox failure is one of the highest risk events in wind turbines. In most of the wind turbines, planetary gearboxes are preferred over conventional gearboxes due to their significant advantages. But condition monitoring of planetary gearboxes present a huge challenge to the vibration analysts due to complex design and construction of its unit, vibration transducer type and locations, wide frequency range of the vibrations, resolution required to separate frequencies and dynamic range required to observe both low frequency and high frequency components in the spectrum. Due to strong Gear Mesh Frequency (GMF) signals, gear defect vibration characteristics can often be suppressed in the overall vibration signal. So there is a need to develop or utilize various special signal processing techniques in order to identify and monitor the progression of defects in gears more effectively. This paper focuses on one such technique namely Sideband Energy Ratio ( SER ) for monitoring of gear defect progression in wind turbine gearboxes. Theory behind SER is and its significance in gear defect monitoring is presented in this paper through three case studies. In all the three case studies, SER of 2XGMF were found to be more sensitive than 1XGMF towards gear defect progression.